Efficacy and safety of once-yearly zoledronic acid in Japanese patients with primary osteoporosis: two-year results from a randomized placebo-controlled double-blind study (ZOledroNate treatment in Efficacy to osteoporosis; ZONE study). Issue 1 (January 2017) - Nakamura, T.; Fukunaga, M.; Nakano, T.; Kishimoto, H.; Ito, M.; Hagino, H.; Sone, T.; Taguchi, A.; Tanaka, S.; Ohashi, M.; Ota, Y.; Shiraki, M.
Abstract Summary In a 2-year randomized, placebo-controlled study of 665 Japanese patients with primary osteoporosis, once-yearly administration of zoledronic acid (5 mg) reduced the risk of new morphometric vertebral fractures. Introduction The purpose of this study was to determine the efficacy and safety of once-yearly intravenous infusion of ZOL in Japanese patients with primary osteoporosis. Methods This was a two-year multicenter, randomized, placebo-controlled, double-blind, parallel-group comparative study (ZONE Study). Subjects were 665 Japanese patients between the ages of 65 and 89 years who had prevalent vertebral fracture. Subjects were randomly assigned to receive once-yearly intravenous infusion of 5 mg of ZOL or placebo at baseline and 12 months. Results The 2-year incidence of new morphometric vertebral fracture was 3.0 % (10/330 subjects) in the ZOL group and 8.9 % (29/327) in the placebo group (p  = 0.0016). The 24-month cumulative incidence of new morphometric vertebral fracture was 3.3 % in the ZOL group versus 9.7 % in the placebo group (log-rank test:p  = 0.0029; hazard ratio: 0.35; 95 % confidence interval: 0.17–0.72). The cumulative incidence of any clinical fracture, clinical vertebral fracture, and non-vertebral fracture was significantly reduced in the ZOL group by 54, 70, and 45 %, respectively, compared to the placebo group. At 24 months, ZOL administration increased bone mineral density in the lumbar spine, femoral neck, and total hip (t test:p  < 0.0001). No new adverse events or osteonecrosis of the jaw were observed in this study. Conclusions Once-yearly administration of ZOL 5 mg to Japanese patients with primary osteoporosis reduced the risk of new morphometric vertebral fractures and was found to be safe.